Risk Management and Investment Sustainability in the Era of Economic Uncertainity - Ayu Novitasyari; Eniwawan Silaen; Masno Marjohan (Indonesian Development of Economics and Administration Journal, 2025)
This study examines the relationship between the implementation of risk management and investment sustainability in the face of global economic uncertainty. Well-planned, data-driven risk management, through strategies such as portfolio diversification, the use of financial instruments, and stress testing, has proven effective in enhancing investment stability by mitigating the impact of market volatility. Additionally, integrating Environmental, Social, and Governance (ESG) principles into investment decision-making processes contributes positively to portfolio resilience against external risks and supports long-term investment value growth. This study also highlights the importance of leveraging advanced technologies, such as artificial intelligence and big data, to improve the accuracy of risk analysis, as well as the need for collaboration among various stakeholders to create a sustainable investment ecosystem. The findings are expected to make a significant contribution to both individual and institutional investors in formulating resilient, sustainability-oriented investment strategies amid global economic challenges.